MODERASI UKURAN PERUSAHAAN DALAM MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2019-2022 - Oktaviani, Sherly; Subaida, Ida; Sari, Lita Permata (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Banking has an important role in supporting the economy in a country. Banking is one of the State's financial institutions that is responsible for collecting and distributing funds to the public. The aim of this research is to analyze and test asset structure and liquidity on capital structure using company size as a moderating variable. This research uses quantitative research methods or uses secondary data. The population in this study used banking companies, in total there were 47 companies with a sample of 10 companies. The sampling technique uses non-probability sampling techniques with purposive sampling techniques. The data analysis and hypothesis testing in this research used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart 3.0 application show that asset structure has a significant positive effect on capital structure, the liquidity has a negative but not significant effect on capital structure, the company size is significantly but negatively able to strengthen the influence of asset structure in improving capital structure. Furthermore, the company size is not significant but can positively weaken the influence of liquidity on capital structure.